The influence of experiential marketing on tourist satisfaction, purchase, repurchase and loyalty: The case of Madeira Island - Pinheiro, Raquel Maria Freitas (2021)
Experiential Marketing is a strategy focused on the creation of unique and memorable emotional experiences. This marketing approach enables co-creation and consumer/brand relationships. In destination tourism this strategy is still not well researched. Therefore, the aim of this dissertation is to understand the influence of experiential marketing on purchase intention, repurchase intention, customer satisfaction and customer loyalty, in the context of Madeira Island. To achieve this, the study proposed a conceptual framework applying experiential marketing through Schmitt’s (1999) strategic experiential modules. The correlations established on the framework were based on extensive literature review. The findings revealed that experiential marketing has a positive impact on all four variables. Even though all variables were positively correlated with experiential marketing, the correlation with customer satisfaction produced the stronger results. Furthermore, correlations were also tested between customer satisfaction to repurchase intention and customer loyalty. The results indicated its positive relationship. Accordingly, these results must be acknowledged and acted upon considering its possible positive influence in the tourism industry.